1995
DOI: 10.1007/bf02052450
|View full text |Cite
|
Sign up to set email alerts
|

Observer variability in the assessment of type and dysplasia of colorectal adenomas, analyzed using kappa statistics

Abstract: The interobserver agreement was moderate to almost perfect, but the intraobserver agreement was only fair to moderate. A simpler classification system or a centralization of assessments would probably increase kappa values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 9 publications
10
39
1
Order By: Relevance
“…As shown previously17 20 21 23 (table 3), at baseline we identified a moderate degree of interobserver agreement in assessing architecture and dysplasia grade. In Phase 2, interobserver agreement in assessing architecture improved.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As shown previously17 20 21 23 (table 3), at baseline we identified a moderate degree of interobserver agreement in assessing architecture and dysplasia grade. In Phase 2, interobserver agreement in assessing architecture improved.…”
Section: Discussionsupporting
confidence: 81%
“…Participants were not aware of the uniform distribution in architectures and dysplasia grades across samples. This distribution differs from routine practice, where tubular architecture and low-grade dysplasia are commoner,17 20 23 24 and this limits, to some degree, the extrapolation of the findings to routine practice. For example, most participants underdiagnosed HGD, which could have been a result of their expected bias of seeing HGD less frequently.…”
Section: Discussionmentioning
confidence: 75%
“…Studies grading dysplasia in ulcerative colitis and colonic adenomas produced an overall agreement between any two pathologists ranging from 42 to 65%. 12,13 Similar studies demonstrated agreement of between 58 and 61% for oesophageal dysplasia 14 and 54% for laryngeal dysplasia. 15 Furthermore, the removal of tissue samples can have a damaging effect on the function of the organ, especially in sensitive organs such as the larynx, where permanent loss of voice may result.…”
Section: Introductionsupporting
confidence: 52%
“…A ð 80 ultra-long working distance lens was used to focus the laser beam (power at the sample of 32 š 1.1 mW) to a spot size of 2-3 µm on the tissue surface and collect the scattered photons in non-confocal mode. At least five spectra were acquired from each larynx sample (mean number D 7.96, range 5-12) and a minimum of 10 spectra were acquired from each oesophagus sample (mean number D 14, range [10][11][12][13][14][15][16][17][18][19][20]. The scattered Raman signal was integrated for 30 s and measured over a spectral range of 400-1800 cm 1 with respect to the excitation frequency.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Cancer was found in 4 (0.05%) of the diminutive polyps and in none of the small polyps. Pickhardt et al 18 [21][22][23][24][25] A recent study also found only moderate interobserver agreement (kappa ϭ 0.53) in pathologists abilities to diagnose any advanced histological features (villous features or high-grade dysplasia) in polyps Ͻ10 mm. 26 In addition, previous studies have not found either feature to be a consistent, independent predictor of subsequent advanced adenoma development.…”
Section: Discussionmentioning
confidence: 97%